“COMMUNICATION STRATEGY OF STARBUCKS INDONESIA'S IN RESPONDING TO THE CRISIS AND REBUILDING BRAND REPUTATION” - Sri Wulandari; Nur Ridwan; Windu Tiastuti; Dian Berliansyah Putra (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Starbucks Indonesia is independently operated by PT Sari Coffee Indonesia and has no direct affiliation with United States foreign policy or geopolitical conflicts involving Israel and Palestine. However, Starbucks remains the target of a consumer boycott in Indonesia due to the widespread and global issues. Starbucks also experienced a communication crisis management, which left customers wavering and its reputation severely shaken. As a result, Starbucks suffered losses and several stores were closed. The method used in this study is a qualitative method to reveal the steps taken by Starbucks Indonesia in overcoming the crisis. Through analysis of social media content and official company statements, it was found that Starbucks Indonesia emphasized transparency, clarification of neutral positions on political issues, and a commitment to the value of diversity. Communication strategies on social media became a primary tool in shaping a positive narrative and strengthening a humanistic brand image. Data collection was carried out from various official online media news sources, social media, official company statements, journal articles, and references from various websites. The results of the study indicate that Starbucks successfully restored its reputation and still enjoys the trust of the Indonesian public in general. These findings contribute to academic understanding regarding the application of SCCT theory and serve as a practical reference for companies facing reputational crises